Implementasi Job Safety Analysis dan HIRARC untuk Mencegah Kecelakaan Kerja Karyawan di PT XYZ - Aldion, Aldion; Kurniawan, Rachman Catur; Suri, Anita (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the implementation of JSA and HIRARC to prevent workplace accidents at PT. XYZ. The method used in this study is qualitative. The data used are primary and secondary data. Secondary data were obtained from observations and documentation, in the form of workplace accident data from January to August 2025. Primary data were collected through direct observation in the work area and interviews with operators. The results of this study indicate that hazard identification using JSA was caused by not using PPE correctly, not checking machines regularly, and not having guidelines or training. Then, through the HIRARC method, of the 11 activities carried out, 8 activities had a medium risk level and 3 activities had a highrisk level.